And their contribution to the prevention of environmental problems - Loayza Perez, Jorge (2013)
This article aims to provide a new concept of industrial processes, the so-called sustainable industrial processes that are used in industrial plants and competitive companies responsible for developing chemicals. These innovative processes should incorporate in its design stages that are efficient, producing less waste and scrap, not pollute the environment, using substances which are safe, and the products and by-products produced by them. These processes must be safe, both internally (for workers) and externally (for communities and ecosystems) and must contribute to sustainable development, ensuring the efficient use of natural resources and promoting the use of renewable resources. An example is the production cellulose pulp that is produced throughout Latin America (Brazil, Argentina and Uruguay), but a sustainable industrial process can be developed nationally.